2019
DOI: 10.1038/s41392-019-0038-9
|View full text |Cite
|
Sign up to set email alerts
|

Targeting EGFR exon 20 insertion mutations in non-small cell lung cancer

Abstract: Inframe insertions of three or more base pairs in exon 20 of the epidermal growth factor receptor ( EGFR) gene were among the first EGFR mutations to be identified as oncogenic drivers in non-small cell lung cancer (NSCLC). However, unlike the classical EGFR L858R point mutation or exon 19 deletions, which represent the majority of EGFR mutations in NSCLC, low frequency EGFR exon 20 insertion muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
240
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(243 citation statements)
references
References 95 publications
(115 reference statements)
2
240
0
1
Order By: Relevance
“…In contrast, both EGFR L858R and exon 19 deletion reduce the affinity of EGFR for ATP, but at the same time have elevated affinity for and are thus sensitive to the first‐generation EGFR inhibitors erlotinib and gefitinib (hereafter E/G) . EGFR exon20ins is also activating, but does not reduce ATP affinity or enhance E/G affinity .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, both EGFR L858R and exon 19 deletion reduce the affinity of EGFR for ATP, but at the same time have elevated affinity for and are thus sensitive to the first‐generation EGFR inhibitors erlotinib and gefitinib (hereafter E/G) . EGFR exon20ins is also activating, but does not reduce ATP affinity or enhance E/G affinity .…”
Section: Discussionmentioning
confidence: 99%
“…Insertions in EGFR exon 20 (encoding amino acids E762‐K823) are typically two or three amino acids and recur at the highly conserved 770–772 residues. As studied in the context of NSCLC, these insertions occur in the C‐helix and loop following the C‐helix and drive the kinase domain to reside in active conformation, but with minimal effect on the ATP binding pocket .…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have reported that rare EGFR mutations can be more effectively targetable with appropriate TKIs [15]. Similarly, several recent studies have reported that insertions in EGFR exon 20, which had been known to be resistant to first-or second-generation EGFR TKI treatments, could be effectively targeted using new TKIs, such as poziotinib [16][17][18]. Therefore, rare EGFR mutations could be equally important targets in the treatment of advanced-stage lung cancer, and detailed information regarding EGFR mutation type is needed to apply appropriate therapies.…”
Section: Discussionmentioning
confidence: 99%
“…However, the impact of this discrepancy on patient care is very low, as efficient and approved therapies are missing for those mutations [20,21]. Thus, these very rare mutations were not reported to be actionable for the different TKIs [22][23][24]. It is important to be aware of the possibility of obtaining a false-negative EGFR mutation using the Idylla device, however, only one discrepancy on druggable alterations was observed, highlighting the reliability of the Idylla device [25].…”
Section: Discussionmentioning
confidence: 99%